Planning climate adaptation in agriculture - Kissinger, Gabrielle; Lee, D.; Narasimhan, P; King’uyu, SM; Sova, Chase; Orindi, VA (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2013)
This meta-synthesis of national climate change adaptation plans, policies and processes spans twelve countries at various stages of adaptation planning and implementation, in three priority CCAFS regions: West Africa (Burkina Faso, Ghana, Mali, Niger, Sénegal), East Africa (Ethiopia, Kenya, Tanzania, Uganda) and South Asia (Bangladesh, India, Nepal). The national adaptation plan (NAP) process was established in the Cancún Adaptation Framework by the United Nations Framework Convention on Climate Change (UNFCCC) to help facilitate effective medium- and long-term adaptation planning and implementation in developing countries, and in particular Least Developed Countries (LDCs). The scope of this review focused primarily on climate adaptation in the agriculture sector, but also included consideration of related sectors, such as water, forests and land use.